The Iconography of Light in Renaissance Painting and its Medieval Heritage - Oana-Maria Nicuță (Anastasis: Research in Medieval Culture and Art, 2022)
The transformations that occurred towards the end of mature Gothic in western Europe drastically changed the use of light in the arts. With the so-called international Gothic and the Italian ProtoRenaissance, light will change its very form of manifestation, replacing the three-dimensional, environmental use of light as a medium with a two-dimensional representation contained within the painting. Using examples from Fra Angelico, Masaccio, Criveli, Vivarini, Titian or Leonardo da Vinci, we will try to show not only how important light was as an iconographic motif, but also how a certain iconography of light was built within bi-dimensional space.